Are stabilization programs expansionary? - Echenique, Federico; Forteza, Alvaro (Estudios Económicos de El Colegio de México, 2000)
The empirical evidence presented in this paper casts doubts on the by now widely accepted “fact” that exchange rate based stabilization programs are expansionary. Even though these programs were associated with output booms, no evidence was found to support the thesis that the booms were caused by the stabilization programs. Rather, positive external shocks seem to have caused both the output booms and the stabilization programs.